Does prolonged grief treatment foster posttraumatic growth? Secondary results from a treatment study with long‐term follow‐up and mediation analysis. (24th July 2017) - Bartl, Helga; Hagl, Maria; Kotoučová, Michaela; Pfoh, Gabriele; Rosner, Rita
Abstract : Objectives: Prolonged grief disorder (PGD) is a persistent and disabling kind of grief reaction that can be treated effectively with psychotherapeutic interventions. There has been limited investigation of whether these interventions can also enhance positive outcomes of bereavement, such as posttraumatic growth or benefit finding. Design: As part of secondary analyses in a randomized controlled trial evaluating integrative cognitive‐behavioural therapy for PGD (PG‐CBT), the posttraumatic growth trajectories in 51 outpatients with clinically relevant prolonged grief symptoms were followed up from baseline up to 1.5 years. Methods: Immediate treatment effects on posttraumatic growth in comparison with a waiting list control group were evaluated with univariate ANCOVA. Using mediation analysis, we examined the relation between symptom reduction and the short‐term treatment effect on posttraumatic growth. For evaluating long‐term outcome stability, the immediately treated group and the delayed treatment group were pooled. Results: PG‐CBT significantly fostered growth in patients suffering from PGD, with a controlled medium effect size of Cohen's d = 0.60 (completer analysis). This effect remained stable up to the 1.5‐year follow‐up. Grief symptom reduction mediated short‐term treatment effects on posttraumatic growth. However, growth also partially mediated treatment effects on prolonged grief symptoms. Conclusions: Taken together, PG‐CBT was effective in enhancing the participants' perception of posttraumatic growth, but the definite interaction between symptom reduction and posttraumatic growth remains unclear, as both seemed to influence each other's trajectory in the course of treatment. Practitioner points: Integrative CBT for prolonged grief disorder also fostered posttraumatic growth. Post‐treatment and 1.5‐year follow‐up effect sizes for posttraumatic growth were moderate. Whether growth‐enhancing techniques are useful in grief treatment needs further research.